Climate Change, Intercropping, Pest Control and Beneficial Microorganisms 2009
DOI: 10.1007/978-90-481-2716-0_15
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Carbamate in Foods and Beverages – A Review

Abstract: Foods and beverages contain many toxic chemicals that raise health concerns. Ethyl carbamate (EC) or urethane is the ethyl ester of carbamic acid. It occurs at low levels, from ng/L to mg/L, in many fermented foods and beverages. EC is genotoxic and carcinogenic for a number of species such as mice, rats, hamsters and monkeys. It has been classified as a group 2A carcinogen, "probably carcinogenic to humans", by the World Health Organization's International Agency for Research on Cancer (IARC) in 2007. The ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 86 publications
(101 reference statements)
2
61
0
1
Order By: Relevance
“…Similar results on free arginine (8.2–77.6 and 73.4–586.2 mg/kg in rice and wheat Qu, respectively) and urea (3.3–6.6 and 19.1–29.7 mg/kg in rice and wheat Qu, respectively) were previously reported . It has been demonstrated that a greater amount of arginine during fermentation could be catabolized to generate more urea after being taken into the yeast cell, and this could result in even more EC formed in the final wine product . In addition, the wheat Qu contained more protein than the rice, which indicates a potential resource for EC formation, as total amino acids are also possible indirect precursors of EC .…”
Section: Resultssupporting
confidence: 84%
“…Similar results on free arginine (8.2–77.6 and 73.4–586.2 mg/kg in rice and wheat Qu, respectively) and urea (3.3–6.6 and 19.1–29.7 mg/kg in rice and wheat Qu, respectively) were previously reported . It has been demonstrated that a greater amount of arginine during fermentation could be catabolized to generate more urea after being taken into the yeast cell, and this could result in even more EC formed in the final wine product . In addition, the wheat Qu contained more protein than the rice, which indicates a potential resource for EC formation, as total amino acids are also possible indirect precursors of EC .…”
Section: Resultssupporting
confidence: 84%
“…Ethyl carbamate (EC) is a byproduct generated during fermentation process that belongs to the 2A group of carcinogen (Beland et al, 2005;Coulon et al, 2006). It is widely persisted in brandy, bread, yogurt, Chinese rice wine, and traditional condiment soy sauce (Battaglia et al, 1990;Matsudo et al, 1993;European Food Safety Authority, 2007;Koh & Kwon, 2007;Weber & Sharypov, 2009). EC is formed from various precursors (Ough et al, 1988) through a reaction promoted by heat and acid condition with ethanol (Kitamoto et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…2005). As it is found in most alcoholic beverages in the μg l −1 range (Weber and Sharypov 2009), exposure to EC may be increased by the regular consumption of alcoholic beverages, and this may be a factor involved in human cellular mutagenesis and resultant tumorigenesis (Zimmerli and Schlatter 1991; Park et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EC has been shown to cause various cancers in a variety of test animals (Leithauser et al 1990;Schlatter and Lutz 1990;Hubner et al 1997;Beland et al 2005). As it is found in most alcoholic beverages in the lg l )1 range (Weber and Sharypov 2009), exposure to EC may be increased by the regular consumption of alcoholic beverages, and this may be a factor involved in human cellular mutagenesis and resultant tumorigenesis (Zimmerli and Schlatter 1991;Park et al 2009). As a result, winemakers have been actively reducing EC levels in wines by both agricultural practices, wine-making practices and, more recently, molecular biological means (Kitamoto et al 1991;Butzke and Bisson 1998;Yoshiuchi et al 2000;Park et al 2001;Schehl et al 2007).…”
Section: Introductionmentioning
confidence: 99%